MAKNA SIMBOLIS TARI MAYANG RONTEK DI KABUPATEN MOJOKERTO - windi Dwi Setya Agustin; Sri Hadi (Greget, 2019)
This research focuses on the symbolic meaning contained in the Mayang Rontek dance. Mayang Rontek Dance is an entertainment dance that was rushed by the young women. The problem in this research is how the idea of Mayang Rontek dance in Mojokerto Regency?. How to form Mayang Rontek dance performances in Mojokerto?. And how the symbolic meaning of Mayang Rontek dance in Mojokerto Regency?. The research was conducted with qualitative research with using a descriptive analysis method used to and analyzing the dance and technique of Mayang Rontek Library, observation and interview data collection. Analyzing the line using the concept of Rahayu Supanggah stating that the garrison involved several elements of mutual such as: Garap, penggarap, facility, furniture or dear and a crisp consideration. To analyse the shape with the concept of a form of Suzanne K With the theories of elements in the dance expressed by the Sumandiyo Hadi. To explain the symbolic meaning of dance Mayang Rontek. The theory of Roland Barthes states that symbols on Objects not only carry information, but also conjugation Structured system of the mark. The results of the research are known to working on idea originated from Manten Mojoputri composed by Setu den other Mojokerto artists. Mayang Rontek Dance contains symbolic significance about the values life. It is included in elements such as: motion, Accompaniment/poetry, dancer, fashion and title. Moreover motion in dance Mayang Rontek is a new style taken from a variety of movements Remo Jombang, Remo Surabaya and Beskalan.Keywords: Mayang Rontek, Garap, form, Setu, symbolic meaning.